Autobiographical odor memory - Willander, Johan (Stockholms universitet, Psykologiska institutionen, 2007)
In the present thesis, three empirical studies investigate autobiographical odor memory with regard to: (a) whole life-span age distributions, (b) phenomenological experience, (c) semantic processing, and (d) odor imagery. Study I explored potential influences of cue type (words, pictures, odors) on the retrieval of autobiographical memories. The results indicated that odor-evoked events were older than memories evoked by words and pictures. The bump for olfactory evoked information peaked in the first decade of life (<10 years of age), whereas the bump of the word- and picture-evoked age distributions peaked in the second decade (i.e., 11-20 years of age). Also, olfactory evoked events were associated with stronger feelings of being brought back in time. Study II investigated the influence of verbal processing on the retrieval of autobiographical olfactory information. The results revealed that semantic knowledge (i.e., the odor name) affected both the age distribution and phenomenological experience. Also, olfactory memories were associated with a higher emotional arousal. Study III addressed the influences of olfactory imagery on the age distribution and phenomenological experiences. The results showed that events evoked by odor imagery were older than memories evoked by words. No differences in phenomenological experiences were found between the two cue conditions. Based on these findings, it is suggested that (a) memories evoked by olfactory information are older than memories evoked by verbal and visual information, (b) odor memories are more emotional and associated with stronger feelings of being brought back in time, (c) knowledge of an odor’s name produces a shift from a more perceptually to a more conceptually driven retrieval, and that (d) imagined odor cues mimic the age distribution of events evoked by real odors. Overall, the results suggest that memories triggered by the olfactory sensory system are different from memories evoked by verbal or visual information.